2021
DOI: 10.5009/gnl20070
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcomes of Borderline Resectable Pancreatic Cancer According to the Neoadjuvant Chemo-Regimens: Gemcitabine versus FOLFIRINOX

Abstract: Background/Aims: Although many studies have reported the promising effect of neoadjuvant treatment for borderline resectable pancreatic cancer (BRPC) to increase resectability, only a few studies have recommended the use of firstline chemotherapeutic agents as neoadjuvant treatment for BRPC. The current study compared clinical outcomes between gemcitabine and FOLFIRINOX (5-fluorouracil, leucovorin, oxaliplatin, and irinotecan) in patients with BRPC. Methods: In this single-center retrospective study, 100 BRPC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Evidence from the literature suggests that adequate chemotherapy, independent of resection status, can increase progression-free survival, which strongly correlates with increased overall survival [ 27 ]. There also appears to be a greater survival benefit with higher potency regimens than lower potency regimens, even in patients with locally advanced and metastatic tumors [ 20 , 28 , 29 ]. Since the use of high-potency chemotherapy is dependent on optimal performance status, considering a patient’s functional capacity could help guide the use of invasive staging.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from the literature suggests that adequate chemotherapy, independent of resection status, can increase progression-free survival, which strongly correlates with increased overall survival [ 27 ]. There also appears to be a greater survival benefit with higher potency regimens than lower potency regimens, even in patients with locally advanced and metastatic tumors [ 20 , 28 , 29 ]. Since the use of high-potency chemotherapy is dependent on optimal performance status, considering a patient’s functional capacity could help guide the use of invasive staging.…”
Section: Discussionmentioning
confidence: 99%
“…Paniccia et al [ 34 ] reported the outcomes of BR patients treated with neoadjuvant FOLFIRINOX: 94% underwent R0 resection and, with a median follow-up of 14.5 mo, median OS was not yet reached. Several other studies demonstrating the efficacy of FOLFIRINOX as neoadjuvant treatment for BR-PDAC have been published[ 35 , 36 ].…”
Section: Choice Of Neoadjuvant Regimen For Br-pdacmentioning
confidence: 99%
“…The primary treatment method for resectable locally advanced pancreatic cancer (LAPC) remains surgery followed by adjuvant chemotherapy with/without adjuvant radiation 6 . Multiagent chemotherapy, such as FOLFIRINOX (oxaliplatin, irinotecan, leucovorin, fluorouracil) or gemcitabine/abraxane, followed by fluoropyrimidine‐based concurrent chemoradiotherapy (CCRT) and surgery or gemcitabine‐based CCRT and medical surgery, is the treatment paradigm for borderline resectable LAPC 7 . CCRT, 125 I seed implantation combined with chemotherapy (125IC), and chemotherapy alone (CA) are all common treatment options for unresectable LAPC, but the best treatment option is still up for debate.…”
Section: Introductionmentioning
confidence: 99%
“…6 Multiagent chemotherapy, such as FOLFIRINOX (oxaliplatin, irinotecan, leucovorin, fluorouracil) or gemcitabine/abraxane, followed by fluoropyrimidine-based concurrent chemoradiotherapy (CCRT) and surgery or gemcitabine-based CCRT and medical surgery, is the treatment paradigm for borderline resectable LAPC. 7 CCRT, 125 I seed implantation combined with chemotherapy (125IC), and chemotherapy alone (CA) are all common treatment options for unresectable LAPC, but the best treatment option is still up for debate. Some trials, such as the ECOG 4201 trial, have shown that CCRT improves overall survival (OS) over CA.…”
Section: Introductionmentioning
confidence: 99%